Rigor and Respect: Recruitment Strategies for Engaging Vulnerable Populations in Research - O’Brien, Jennifer E. (Journal of interpersonal violence, 2022)
Engaging vulnerable populations in research is a critical focus for researchers seeking to find ways to improve safety and well-being for broader populations. Vulnerabilities often co-occur, meaning that individuals may experience vulnerabilities in multiple facets of their life (e.g., victim of abuse and mental health diagnoses). Unfortunately, many vulnerable populations remain underinvestigated due to difficulty reaching, engaging, and safely including such populations in research. While most researchers assert the importance of including vulnerable populations in research, few actively and successfully recruit them. Many vulnerable populations are understandably weary of research participation. Victims and survivors of domestic minor sex trafficking (DMST) are one such vulnerable population, in that identification may incur substantial risk for DMST victim?s physical safety and well-being. In addition, DMST victims and survivors often experience co-occurring vulnerabilities including substance use, histories of abuse, delinquency, and poor mental health. Accordingly, they are notoriously difficult to recruit for research participation. The current paper uses a detailed case example to describe the recruitment and retention strategies used by one researcher to promote DMST survivor research participation. A candid account of challenges, successes, and lessons learned is offered in service of building methodological techniques for recruitment that both honor participant experiences while championing methodological rigor. Findings detail the importance of trust and a trauma-informed approach to qualitative data collection and analysis. Authors include specific strategies to promote comfort and candor amid traumatic response in ways that may empower research participants. A detailed discussion of how such strategies may be adapted for vulnerable populations beyond DMST victims and survivors is provided.